Norwegian homeowners' debt-servicing capacity is adequate - Kjersti-Gro Lindquist; Haakon Solheim; Bjørn Helge Vatne (Norges Bank, 2022)
Debt-servicing capacity is a function of both available cash flow and the size of obligatory expenses. We use household level information to calculate normal expenses that cover food, other general consumption, electricity and fixed housing expences, as well as interest expenses. We link this to information on household income, debt, financial wealth and housing wealth. Just over 1 percent of home-owning households lacked income to cover normal expenses and interest in 2020. Half of these had the opportunity to cover the liquidity deficit by drawing on financial wealth or increasing their mortgages. We show how higher food and electricity prices, and also higher interest rates, affect the number of households with weak debt-servicing capacity and the share of debt held by this group. The share of households that might experience debt servicing problems will increase with a rapid and marked increase in interest rates. Given the debt-to-income ratio in 2020, it is only when the interest rate rises above 5 percent that the share facing problems rises markedly in groups other than those with the lowest income.
hdl:11250/3036118
Keywords: 330; Immobilienfinanzierung; Kredittilgung; Haushaltsstatistik; Norwegen